Giải phương trình :
\(\sqrt{2x-2+2\sqrt{2x-3}}+\sqrt{2x+13+8\sqrt{2x-3}}=5\)
\(\sqrt{2x-2+2\sqrt{2x-3}}+\sqrt{2x+13+8\sqrt{2x-3}}=7\)
Giải phương trình: \(\sqrt{4x^2-9}=2\sqrt{2x+3}\)
Giải phương trình:
a)\(\sqrt{x+8+2\sqrt{x+7}}+\sqrt{x+1-\sqrt{x+7}}=4\)
b)\(\sqrt{x+\sqrt{2x-5}-2}+\sqrt{x-3\sqrt{2x-5}+2}=2\sqrt{2}\)
giải phương trình:
1) \(\sqrt{5x^2-2x+2}=x+1\)
2) \(\sqrt{4x^2-x+1}-2x=3\)
mng giúp mik 2 câu này được ko. cảm ơn bạn nhiều
giải phương trình
1/\(\sqrt{x^2}-4x+8\) +\(\sqrt{x^2-4x+13}=17-2x^2+8x\)
2/\(\sqrt{3x^2+6x+7}+\sqrt{5x^2+10x-24}=4-2x-x^2\)
giải phương trình \(\sqrt{2x^2-10x+13}+\sqrt{26x^2-24x+8}=4x+1\)
\(\sqrt{2x+2\sqrt{2x-1}}\)+\(\sqrt{2x+3+4\sqrt{2x-1}}\)= 6
Gải phương trình cần gấp
Giải phương trình
a) \(\sqrt{2x+4+6\sqrt{2x-5}}\)+\(\sqrt{2x-4-2\sqrt{2x-5}}\)=4 (1)
b) \(\sqrt{x+2-4\sqrt{x-2}}\)+\(\sqrt{x+7-6\sqrt{x-2}}\)=1 (2)